Popular South African music on dominant local masculine ideals and their influence and societal response to the gender-based violence (GBV) pandemic - Seluleko Eric Ngcobo (Cogent Arts & Humanities)
Abuse against women and minorities is a global issue that requires immediate attention. SA is one of the countries found to be grossly unsafe for women in the world. Current, evidence suggests that one South African woman is killed every hour. In addition, evidence shows that GBV and femicide are rooted in negative masculine ideals. The GBV pandemic rooted on context specific dominant masculine ideas has been mirrored by artists through music in raising awareness. This study draws on a case study qualitative methods to purposively sample Three songs from three South African artists to understand music portrayal of dominat masculine ideals, how they are linked to GBV and artists response to the GBV pandemic. Connell’s theory on masculinities is employed to interpret the findings of this study. The sampled music suggests that Men aspire to work and provide for their families. However, due to rife unemployment, poverty, and inequality, men adopt alternative masculine ideals based on violence, power, money, women, and sex to reinforce and uphold their masculine identities. Artists raise awareness and provide advice to women, neglecting men as an integral part that is involved and play a role in the GBV pandemic. This study concludes that dominant masculine ideals and their influence on GBV are echoed through music. Researchers and musicians should work together to raise awareness about GBV and in ensuring that interventions for GBV include a focus in changing men’s behaviour. This study recommends that artists should focus on men and use thier voice to discourage negative masculine ideals.